الدراسة البنيوية والضوئية والكهربائية لشرائح اكسيد القصدير المطعم بالنحاس - حمروني, نور الدين; بليلة, عبد القادر (My University, 2017)
حى الاهخًاو خلال هزا انعًم بذساست كم يٍ انخصائص انبٍُىٌت ،انكهشبائٍت وانضىئٍت لأغشٍت أكسٍذ انقصذٌش انُقً ) (SnO2وانًطعى بانُحاط ) (Cuبُسب )% ،(1-16ورنك إَطلاقا يٍ كهىسٌذ انقصذٌش)(SnCl2وكهىسٌذ انُحاط)ٌ (CuCl2خى حشسٍب انًحهىل عهى سكائض صجاجٍت ححج دسجت حشاسة ° 480Cنًذة 4دقائق ورنك يٍ خلال حقٍُت انشش بالإَحلال انحشاسي . أظهش إَعشاج الأشعت انسٍٍُت أٌ لأغشٍت أكسٍذ انقصذٌش انًطعى بانُحاط بٍُت يخعذد انخبهىس سباعً انضواٌا وحأخز الإحجاِ انخفضٍهً ).(200 أبذث انُفارٌت انضىئٍت حضاٌذا يٍ % 80.88إنى % ، 88.33أيا انًقاويت انسطحٍت فقذ شهذث اسحفاعا حخى )(1977.410 Ωعُذ َسبت انخطعٍى % . 8حخغٍش قٍى انفاصم انطاقً وفقا نُسب انخطعٍى بانُحاط نٍأخز انقٍى . (4.1680eV) (حخى4.0287eV) ٍيIn this work ,we studied structural, electrical, and optical characterization of undoped tin oxide (SnO2) and cuivre (Cu) doped (SnO2) thin films , Which have been deposited from tin chloride (SnCl2) and cuivre chloride(CuCl2)onto glass substrates by spray pyrolysis technique .Samples were deposited for 4 minutes at the substrate temperature of 480C°.The doping concentration of (Cu) was varied from 1 to 16 wt (%) in solution.X-ray diffraction (XRD) has shown polycrystalline structure according to Tetragonal , Rutile (SnO2) structure with (200) as preferential orientation for cuivre (Cu) doped (SnO2) thin films. The optical transmittance of (SnO2:Cu) films in visible region increases from 76% to 90%.The sheet resistance (Rsh) varied from )672.951Ω) to )6255.460Ω) for Cu-doping in the range 0-8 wt (%).The optical band gap (Eg) increased from (4.09.5eV)to (4.61.0eV)with increasing of the concentration of cuivre (Cu) dopants
مذكرة ماستر فيزياء
Keywords: :أكسٍذ انقصذٌش ) ، (SnO2انشش بالإَحلال انحشاسي ، الأغشٍت انشقٍقت ،انُحاط )(Cu إَعشاج الأشعت انسٍٍُت , انفاصم انطاقً, انًقاويت انسطحٍت